RNA-seq-based evaluation of bicolor tepal pigmentation in Asiatic hybrid lilies (Lilium spp.). (December 2016) - Suzuki, Kazuma; Suzuki, Tomohiro; Nakatsuka, Takashi; Dohra, Hideo; Yamagishi, Masumi; Matsuyama, Kohei; Matsuura, Hideyuki
Abstract Background Color patterns in angiosperm flowers are produced by spatially and temporally restricted deposition of pigments. Identifying the mechanisms responsible for restricted pigment deposition is a topic of broad interest. Some dicots species develop bicolor petals, which are often caused by the post-transcriptional gene silencing (PTGS) of chalcone synthase (CHS ) genes. An Asiatic hybrid lily (Lilium spp.) cultivar Lollypop develops bicolor tepals with pigmented tips and white bases. Here, we analyzed the global transcription of pigmented and non-pigmented tepal parts from Lollypop, to determine the main transcriptomic differences. Results De novo assembly of RNA-seq data yielded 49, 239 contigs (39, 426 unigenes), which included a variety of novel transcripts, such as those involved in flavonoid-glycosylation and sequestration and in regulation of anthocyanin biosynthesis. Additionally, 1258 of the unigenes exhibited significantly differential expression between the tepal parts (false discovery rates <0.05). The pigmented tepal parts accumulated more anthocyanins, and unigenes annotated as anthocyanin biosynthesis genes (e.g., CHS, dihydroflavonol 4-reductase, andanthocyanidin synthase ) were expressed 7–30-fold higher than those in non-pigmented parts. These results indicate that the transcriptional regulation of biosynthesis genes is more likely involved in the development of bicolor lily tepals rather than the PTGS ofCHS genes. In addition, the expression level of a unigene homologous toLhMYB12, which often regulates full-tepal anthocyanin pigmentation in lilies, was >2-fold higher in the pigmented parts. Thus, LhMYB12 should be involved in the transcriptional regulation of the biosynthesis genes in bicolor tepals. Other factors that potentially suppress or enhance the expression of anthocyanin biosynthesis genes, including aWD40 gene, were identified, and their involvement in bicolor development is discussed. Conclusions Our results indicate that the bicolor trait of Lollypop tepals is caused by the transcriptional regulation of anthocyanin biosynthesis genes and that the transcription profile ofLhMYB12 provides a clue for elucidating the mechanisms of the trait. The tepal transcriptome constructed in this study will accelerate investigations of the genetic controls of anthocyanin color patterns, including the bicolor patterns, ofLilium spp.